MEMBANGUN KEPEMIMPINAN YANG MENYENANGKAN - Suryana, Asep (Universitas Pendidikan Indonesia, 2014)
Leadership is the ability to drive, steer, even forcing people to move towards achieving the goal. Leadership much to appear in a variety of styles, the style is in the form of behavior that appear to form a task orientation, human relations, spiritual, social, democratic, authoritarian and others. The problem, whether the leadership ditampilkannyacukup deemed satisfactory and enjoyable for all orang.Kepemipinan unpleasant to have the possibility of moving in together all components in the organization became minimal.Menyenangkan quite perceptional, has a sense of fun that vary depending on the point where the interaction takes place. However, there is one corner of the realignment that leadership must be able to foster a sense of security, certainty on the job, the assuredness of life, and improving the quality of work. The construction, arrangement must be made through the